2018
DOI: 10.3892/or.2018.6206
|View full text |Cite
|
Sign up to set email alerts
|

Application of multifunctional nanomaterials in cancer vaccines (Review)

Abstract: Tumor immunotherapy has been in development for more than a century. With the rapid developments in biotechnology research in recent years, immunotherapy has become a promising oncotherapy strategy after surgery, chemotherapy and radiotherapy. Cancer vaccines are a promising new treatment strategy and the application of nanotechnology in cancer vaccines, greatly enhances their effectiveness. Such applications indicate the bright prospects of tumor immunotherapy. The multifunctional nanomaterials used in cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…of tumour vaccines, NPs have greatly improved the efficacy of vaccines and reduced the number of drug administrations (Sulczewski et al, 2018;Wadhwa et al, 2020). Many studies have reported the preparation of synthetic vaccines based on NPs; such vaccines have the potential to enhance the corresponding immune response (lymph node transport efficiency) and improve vaccine delivery (Fu et al, 2018;Kheirollahpour et al, 2020). Zhuang et al (Zhuang et al, 2016) used lipid-enveloped zinc phosphate hybrid (LZnP) NPs to deliver polypeptides (TRP2180-188 and HGP10025-33) and Toll-like receptor 4 agonists.…”
Section: Application Of Nps In Vaccinesmentioning
confidence: 99%
“…of tumour vaccines, NPs have greatly improved the efficacy of vaccines and reduced the number of drug administrations (Sulczewski et al, 2018;Wadhwa et al, 2020). Many studies have reported the preparation of synthetic vaccines based on NPs; such vaccines have the potential to enhance the corresponding immune response (lymph node transport efficiency) and improve vaccine delivery (Fu et al, 2018;Kheirollahpour et al, 2020). Zhuang et al (Zhuang et al, 2016) used lipid-enveloped zinc phosphate hybrid (LZnP) NPs to deliver polypeptides (TRP2180-188 and HGP10025-33) and Toll-like receptor 4 agonists.…”
Section: Application Of Nps In Vaccinesmentioning
confidence: 99%
“…Apart from the physical and chemical attributes of nanocarriers, other potential features that focus on multiple deliveries wherein multiple attributes can be targeted through an administered route required for effective nano-immunotherapy. This includes immunomodulatory or adjuvant molecules coupled with tumor antigens, raising the levels of nano-immunotherapy [99][100][101]. Studies in in vivo melanoma mouse model demonstrate antitumor and immunoregulatory nature of melittin (specialized bee venom from Europe).…”
Section: Nano-assisted Cancer Vaccinesmentioning
confidence: 99%
“…Vaccine delivery based on nanoparticles (NPs) overcomes the limitations of the instability of soluble macromolecular components, low cellular internalization of soluble materials, and unsatisfactory cross-presentation of cytotoxic T cells. , Therefore, the therapeutic use of nanodelivery systems for vaccine carriers results in enhanced immunotherapy efficiency against tumor cells. Nanomaterials with inherent immunostimulatory properties are advantageous in the case of tumor vaccines, enabling them to function as nanoadjuvants, helping to promote the initiation of immune responses. , Various nanomaterials have been developed as nanoadjuvants used in nanovaccine-based immunotherapy, including calcium phosphate, zinc oxide, mesoporous silicon, etc . Nevertheless, the current immune adjuvants still have various problems.…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials with inherent immunostimulatory properties are advantageous in the case of tumor vaccines, enabling them to function as nanoadjuvants, helping to promote the initiation of immune responses. 25,26 Various nanomaterials have been developed as nanoadjuvants used in nanovaccinebased immunotherapy, including calcium phosphate, 27 zinc oxide, 28 mesoporous silicon, 29 etc. Nevertheless, the current immune adjuvants still have various problems.…”
Section: ■ Introductionmentioning
confidence: 99%